Computer-based system and security controls over accounting information - Mohamed, Intan Salwani; Mohd Daud, Norzaidi (Institute of Research Development and Commercialization, 2004)
This study investigates how certain factors—specifically the level of computer usage, types of software usage, and the size of the accounting department—in a computer-based accounting system influence the level of organizational commitment to security controls. Companies registered with the Companies Commission of Malaysia (CCM) under Group 7 (technology, communications, and transportation) constitute the population of interest. The results indicate that non-accounting software usage and the size of the accounting department significantly explain the variance in organizational commitment to security controls. Conversely, the level of computer usage and accounting software usage were found to have no significant relationship with organizational commitment to security controls.